MINAT BELAJAR SISWA KELAS X PADA MATA PELAJARAN DASAR DESAIN DI SEKOLAH MENENGAH KEJURUAN : minat belajar, dasar desain - Irawati, Rindang; Andayani, Sri Wahyu (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine (1) class X student’s interest in basic design subjects, (2) the learning interest of class X students in basic design subjects is seen from internal factors, (3) the learning interest of class X students in basic design subjects at SMK N 2 Godean seen from external factors. This research is quantitative and descriptive. This study's population was all class X fashion design students with a total of 106. The research sample is 51 students. Data collection using observation and questionnaires.Data analysis using standard deviation. The research results show (1) the learning interest of class X students in basic design subjects is in the moderate category with a relative frequency of 49,01%, (2) the learning interest of class X students in basic design subjects seen from internal factors is in the sufficient category with a relative frequency of 49,01%, (3) the learning interest of class X students in basic design subjects seen from external factors is in the sufficient category with a relative frequency of50,98%.